Novel Pyrimidine Derivatives Bearing a 1,3,4-Thiadiazole Skeleton: Design, Synthesis, and Antifungal Activity - Pan, Nianjuan; Liu, Chunyi; Wu, Ruirui; Fei, Qiang; Wu, Wenneng (Frontiers in Chemistry, 2022)
In this study, twenty novel pyrimidine derivatives bearing an 1,3,4-thiadiazole skeleton were designed and synthesized. Then their antifungal activity against Botrytis cinereal (B. cinereal), Botryosphaeria dothidea (B. dothidea), and Phomopsis sp. were determined using the poison plate technique. Biological test results showed that compound 6h revealed lower EC50 values (25.9 and 50.8 μg/mL) on Phompsis sp. than those of pyrimethanil (32.1 and 62.8 μg/mL).